“Conservación por mínimo proceso de la piña (ananás comosus), en rodajas y tiras” - Pasquel Réategui, José Luis (2009)
Research in pineapple (Ananas comosus), are about juice pasteurised and concentrated, frozen and products dried, without .antecedentes conservation through minimal processing or fourth range. The greater part of the consumption of the fruit is in fresh and juice, but is sees limited by the difficult handling post harvest and the bare of the fruit, the processing minimum or food of the IV range, can be an interesting alternative of market, to its demand. The objective of this research was to provide to the consumer a fruit product (pineapple), very similar fresco with a long service life and at the same time, to guarantee the .seguridad of them, maintaining a solid nutritional and sensory quality under different concentrations of citric acid. The work was developed in the pilot plant of. Fruits and vegetables of the Faculty of agro-industrial engineering of the National University of San Martín - Tarapoto, following the continued...